Design of a silicon Mach–Zehnder modulator via deep learning and evolutionary algorithms - Aparecido de Paula, Romulo; Aldaya, Ivan; Sutili, Tiago; Figueiredo, Rafael C.; Pita, Julian L.; Bustamante, Yesica R. R. (Scientific reports, 2023)
As an essential block in optical communication systems, silicon (Si) Mach–Zehnder modulators (MZMs) are approaching the limits of possible performance for high-speed applications. However, due to a large number of design parameters and the complex simulation of these devices, achieving high-performance configuration employing conventional optimization methods result in prohibitively long times and use of resources. Here, we propose a design methodology based on artificial neural networks and heuristic optimization that significantly reduces the complexity of the optimization process. First, we implemented a deep neural network model to substitute the 3D electromagnetic simulation of a Si-based MZM, whereas subsequently, this model is used to estimate the figure of merit within the heuristic optimizer, which, in our case, is the differential evolution algorithm. By applying this method to CMOS-compatible MZMs, we find new optimized configurations in terms of electro-optical bandwidth, insertion loss, and half-wave voltage. In particular, we achieve configurations of MZMs with a 40 GHz bandwidth and a driving voltage of 6.25 V , or, alternatively, 47.5 GHz with a driving voltage of 8 V . Furthermore, the faster simulation allowed optimizing MZM subject to different constraints, which permits us to explore the possible performance boundary of this type of MZMs.